EKOLOGI TEMPAT TUMBUH SARANG SEMUT PADA TAMAN WISATA ALAM GUNUNG MEJA MANOKWARI - Endria Sada; Rima Herlina S. Siburian; Novita Panambe (EnviroScienteae, 2018)
The ant-plant Sarang Semut is one of the medicinal antimicrobial plants that is very beneficial to human health. As such the plant has widely been exploited in their natural habitat. The silviculture of this plant is not available due to limited knowledge about the existence in nature. Therefore, it is imperative to undertake the ecological study on the growth site of this plant in nature to collect the basic information for the culture and cultivation of this plant. The method used in this research was the descriptive method with the survey technique in Gunung Meja Nature Tourism Park, Manokwari.  The research showed that one species of ant-plant was found namely Myrmecodia cf. schlechteri Valeton. The plant is epifit to selective host plants such as  Garcinia picrorrhiza, Sterculia macrophylla, Intsia bijuga, Pometia coreacea, and Antiaris toxicaria. The ideal growth zone of this plant is in Zone 2 and 3.